2010
DOI: 10.1016/j.neuroimage.2009.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Where syntax meets math: Right intraparietal sulcus activation in response to grammatical number agreement violations

Abstract: Previous research has shown that the processing of words referring to actions activated motor areas. Here we show activation of the right intraparietal sulcus, an area that has been associated with quantity processing, when participants are asked to read pairs of words with number agreement violations as opposed to phrases with gender agreement violations or with no violation. In addition, we show activation in the left premotor and left inferior frontal areas when either gender or number agreement is violated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 61 publications
2
39
0
1
Order By: Relevance
“…Such sensitivity has also been reported in electrophysiological studies and neuroimaging studies with respect to both grammatical gender disagreement (e.g., monolinguals: Barber and Carreiras, 2005;Carreiras et al, 2010;Hammer et al, 2007;advanced late learners: Gillon-Dowens et al, 2009;Rossi et al, 2006;Sabourin et al, 2006;Tokowicz and MacWhinney, 2005) and number disagreement (e.g., monolinguals: Carreiras et al, 2010;Barber and Carreiras, 2005; advanced late learners: Rossi et al, 2006;Osterhout et al, 2008;Gillon-Dowens et al, 2009).…”
Section: L2 Spanish Noun Concord Effectsmentioning
confidence: 66%
“…Such sensitivity has also been reported in electrophysiological studies and neuroimaging studies with respect to both grammatical gender disagreement (e.g., monolinguals: Barber and Carreiras, 2005;Carreiras et al, 2010;Hammer et al, 2007;advanced late learners: Gillon-Dowens et al, 2009;Rossi et al, 2006;Sabourin et al, 2006;Tokowicz and MacWhinney, 2005) and number disagreement (e.g., monolinguals: Carreiras et al, 2010;Barber and Carreiras, 2005; advanced late learners: Rossi et al, 2006;Osterhout et al, 2008;Gillon-Dowens et al, 2009).…”
Section: L2 Spanish Noun Concord Effectsmentioning
confidence: 66%
“…In particular, Carreiras et al (2010) investigated agreement in the processing of word pairs, either determiner-noun or noun-adjective Spanish items. They reported increased BOLD activity in the left premotor and left inferior frontal areas for the processing of both number and gender agreement violations as compared to the agreement baseline.…”
Section: Psycho-physiological Evidence: Erp and Fmri Studiesmentioning
confidence: 99%
“…Carreiras, Carr, Barber, and Hernandez (2010) reported activation in the right intraparietal sulcus when participants were asked to read pairs of words with number agreement violations (e.g., los piano [the m-p piano m-s ]) as opposed to phrases with gender agreement violations (e.g., la piano [the f-s piano m-s ]) or with no violation (e.g., el piano [the m-s piano m-s ]). Given that this activation was number specific (i.e., not present for gender violations), it was concluded that it reflected quantity processing.…”
Section: Singular and Plural Nounsmentioning
confidence: 99%
“…So far, there is only one neuroimaging study investigating the processing of grammatical number (Carreiras et al, 2010). However, whereas in the paradigm used by Carreiras et al (2010) participants read word pairs containing grammatical violations, in this study target words are embedded in a context of fluent, grammatical speech presented auditorily, thus avoiding any metalinguistic task demands. Until now, results on the localization of mass and count noun processing rely on EEG experiments and seem partly inconsistent.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation